(untitled) (VETERINARIA, 2020)
Morphological characteristics of the digestive systems in birds are direct reflection of evolutionary adaptations of these animals to different type and way of diet. The research conducted on domestic and some wild birds indicate that besides the evolutionary factors, time of start of food intake after the hatching, and amount and composition of food in the period of intensive growth also influence morphologicalcharacteristics of digestive systems in birds. The aim of this study was to determine the influence of extensive and intensive way of farming, and different types and amount of food on the morphometric characteristics of the small and large intestines in 45 broiler turkeys (BIG BUT 600). Statistical analysis shows that the way of breeding and the type and quantity of food all have significant impact on the body weight in turkeys but do not influence the length of the intestinal tract in these animals.